Aktivisme Gerakan Aksi Kamisan Dalam Memperjuangkan Penyelesaian Hak Asasi Manusia - Ananda Mukhlis Rahma Putra (Epistemik Press, 2020)
The Kamisan Movement is an embodiment of the symbolic action movement, for disclosing injustice in the settlement of human rights cases in Indonesia. This research is based on: 1) unresolved past gross human rights violations; 2) the absence of the political will of the President to resolve human rights violations in Indonesia; and 3) there is an allegation that the government has attempted impunity in the settlement of serious human rights cases in the past. The research method used is descriptive qualitative. The analytical knife in this study uses the theory of social movement dynamics through the perspective of McAdam, McCarthy, and Zald, which consists of: 1) political opportunities; 2) mobilizing structure; and 3) cultural framing. The results of the study concluded that the political opportunity for our action was small due to obstacles in the process of resolving the case. Then the effort to mobilize the masses was successful, the mass of the Kamisan action has expanded to various regions. However, the political mobilization carried out by the Thursday action has not been able to resolve human rights cases in Indonesia. And lastly, the framing of Kamisan has succeeded in portraying its movement as a consistent symbolic action in the settlement of human rights settlements in Indonesia. Then the movement against impunity became the image that was raised by the mass of Thursday's action which was intended to keep human rights cases going on trial. The handling of human rights cases that seem to be ignored by the government kills the values of good governance, where there must be open spaces for civil society, because in the process the value of guaranteeing the rights of citizens. No matter how complicated the resolution of past gross human rights violations is, it cannot be done that no victims should be given.